2016
DOI: 10.5194/acp-16-6841-2016
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic use of Lagrangian dispersion and radiative transfer modelling with satellite and surface remote sensing measurements for the investigation of volcanic plumes: the Mount Etna eruption of 25–27 October 2013

Abstract: Abstract. In this paper we combine SO 2 and ash plume dispersion modelling with satellite and surface remote sensing observations to study the regional influence of a relatively weak volcanic eruption from Mount Etna on the optical and micro-physical properties of Mediterranean aerosols. We analyse the Mount Etna eruption episode of 25-27 October 2013. The evolution of the plume along the trajectory is investigated by means of the FLEXible PARTicle Lagrangian dispersion (FLEXPART) model. The satellite data set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 90 publications
4
50
0
Order By: Relevance
“…Volcanic emissions have important impacts on the atmospheric composition (e.g., [1,2]), cloud distribution (e.g., [3]) and regional (e.g., [4]) to global climate (e.g., [5]). The direct climate forcing of volcanic plumes critically depends on the optical and micro-physical properties of the volcanic aerosols, that in turn depend on the evolution processes of the effluents in the atmosphere [6].…”
Section: Introductionmentioning
confidence: 99%
“…Volcanic emissions have important impacts on the atmospheric composition (e.g., [1,2]), cloud distribution (e.g., [3]) and regional (e.g., [4]) to global climate (e.g., [5]). The direct climate forcing of volcanic plumes critically depends on the optical and micro-physical properties of the volcanic aerosols, that in turn depend on the evolution processes of the effluents in the atmosphere [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clarisse et al, (2014) introduces and validates a new method for the retrieval of SO 2 plume height from IASI measurements using the Nabro 2011 eruption as a case study. Hyperspectral infrared observations (Carboni et al, 2012(Carboni et al, , 2015 and inverse modelling procedures (Moxnes et al, 2014;Boichu et al, 2013Boichu et al, , 2015 have also shown promising results.…”
Section: Accepted M Manuscriptmentioning
confidence: 92%
“…Back-trajectory analysis of volcanic plumes has been performed by Hughes, et al (2012) and Sellitto, et al (2015) with the aim of studying the transport paths of SO 2 clouds produced from …”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…While the project is mostly target to the Central-Eastern Mediterranean, where up to 80% of the Etnean plume disperses [Sellitto et al, 2017], the less downwindventilated Central-Southern Mediterranean region is also explored [Sellitto et al, 2016].…”
Section: Iii2 Smedmentioning
confidence: 99%
“…Etna, thus exerting a significant, episodic radiative forcing [Sellitto et al, 2016], which is critically dependent from chemical/micro-physical processes in atmosphere [Sellitto and Briole, 2015]. The radiative impact is studied with both radiative transfer modelling and satellite observations of radiative fluxes.…”
Section: Iii3 Med-suv Wp5mentioning
confidence: 99%